Photonic nanojet engineering to achieve super-resolution in photoacoustic microscopy: a simulation study - Upputuri, Paul Kumar (2018)
Label-free photoacoustic microscopy (PAM) with nanometric resolution is important to study cellular and sub-cellular structures, microcirculation systems, micro-vascularization, and tumor angiogenesis etc. But, the lateral resolution of a conventional microscopy is limited by optical diffraction. The photonic nanojet generated by silica microspheres can break this diffraction limit. Single silica sphere can provide narrow photonic jet, however its short length and short working distance limits its applications to surface imaging. It is possible to increase the length of the photonic nanojet and its working distance by optimizing the sphere design and its optical properties. In this work, we will present various sphere designs to achieve ultra-long and long-working distance photonic nanojets for far-field imaging. The nanojets thus generated will be used to demonstrate super-resolution photo-acoustic imaging using k-wave simulations. The study will provide new opportunities for many biomedical imaging applications that require finer resolution.